A CASE HISTORY OF KATIGRAHA MANAGED WITH AYURVEDA TREATMENT - Prasanna K.G; Khan Arif J.S; Gayathri R; Annrose P.A (International Journal of Applied Ayurved Research, 2017)
A 36 year old male patient of Katigraha came to our Ayurveda hospital complaining of low back pain, numbness and occasionally stiffness of left lateral aspect of thigh while getting up since 1year but severe since 5 months. The symptoms increased because of over straining and also by day to day activities. Patient was treated as indoor patient for 21days with internal medicines including rasna saptakam kashayam ,trayodasanga guggulu ,dhanwantaram vasti pakam, sukumaram lehyam along with picu and vasti therapy. After completion of the treatment, patient got significant results.